2020
DOI: 10.1186/s12911-020-1027-1
|View full text |Cite
|
Sign up to set email alerts
|

Designing a mHealth clinical decision support system for Parkinson’s disease: a theoretically grounded user needs approach

Abstract: Background: Despite the established evidence and theoretical advances explaining human judgments under uncertainty, developments of mobile health (mHealth) Clinical Decision Support Systems (CDSS) have not explicitly applied the psychology of decision making to the study of user needs. We report on a user needs approach to develop a prototype of a mHealth CDSS for Parkinson's disease (PD), which is theoretically grounded in the psychological literature about expert decision making and judgement under uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…The behavioral features involved in the decision-making process, i.e. how a recommender system may influence physician’s decision making [ 24 ], and how this technology could have a positive impact on patient’s care and better economic management is a problem that not only depends on the technical implementation and the AI component but also on the final user’s interface. For instance, in a recent investigation, it has been shown that , when designed well, recommender systems that incorporate treatment costs can result in significant cost savings, while providing similar or better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral features involved in the decision-making process, i.e. how a recommender system may influence physician’s decision making [ 24 ], and how this technology could have a positive impact on patient’s care and better economic management is a problem that not only depends on the technical implementation and the AI component but also on the final user’s interface. For instance, in a recent investigation, it has been shown that , when designed well, recommender systems that incorporate treatment costs can result in significant cost savings, while providing similar or better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…FinJeHeW 2020;12(3) 164 [19][20][21][22]. There remains a lack of knowledge about PwP perspectives to better understand the factors, technological or otherwise, that influence PwP decisionmaking about mHealth use and its integration into daily life [23,24].…”
Section: 102020mentioning
confidence: 99%
“…For HCP interfaces, the importance of workflow integration to support data-driven consultations has been emphasized [44]. A European Union-funded project has reported on the design of a clinical decision support system for PD that takes a holistic approach, which is in line with the functionalities suggested in this study [45][46][47]. The researchers emphasize the importance of enabling shared decision making [46].…”
Section: Functionalities For Providing Feedback and Recommendationsmentioning
confidence: 67%